A comprehensive review of Trinitor components: A sustainable waste heat recovery polygenerative system for diesel vehicles - Duraivel, Balamurali; Shaik, Saboor; Bansal, Ritik; Khanda, Shubhankar Debabrata; Patel, Dhruv; Natarajan, M.; Saleel, C. Ahamed; Jilte, R. D.; Agbulut, Umit (SPRINGER, 2024)
Internal combustion engine inefficiencies and waste heat emissions raise environmental concerns, as they waste fuel energy in the form of heat, increasing fuel consumption and greenhouse gas emissions. Additionally, waste heat contributes to the urban heat island effect. Waste heat recovery is a vital solution, capturing and repurposing heat to reduce fuel use, emissions, and costs while promoting sustainability, innovation, and economic growth. Polygenerative waste heat recovery maximizes energy efficiency by generating multiple forms of energy from a single source, enhancing overall sustainability. The proposed Trinitor model is a polygenerative system encompassing power generation, product drying, space cooling/heating, and oxygen production. Power generation utilizes exhaust heat stored in a phase change material (PCM) to generate electricity through a Hot Air Turbine. The PCM also stores heat from the PVT thermal collector and supports produce drying. In the space cooling/heating process, the temperature contrast resulting from the hot air generated by the turbine and the cooled air from the Cooling chamber is harnessed by the Seebeck principle within the TEG, converting heat energy into electricity, and it is possible to create temperature variations using the Peltier Effect by supplying electricity. Oxygen production involves dehumidifying air, separating oxygen from hydrogen using an electrolyzer and storing oxygen for civilian use. A component review identifies SiC wall flow-diesel particulate filters (DPF), a paraffin-based Latent Heat Storage System, and electric-assisted turbo compounding as cost-effective for energy production. Produce drying relies on hot air or infrared drying, a revolving wicks humidifier, and a cooling coil dehumidifier. Space cooling/heating needs a water-type PV/T collector, MPPT charge controller, lithium-ion batteries, and ceramic TEGs. A PEM electrolyzer with appropriate components (bipolar plates, electrodes, catalyst, membrane, and gasket) enhances oxygen production efficiency. Based on existing literature, the trinitor has the potential to attain an overall efficiency ranging from 40.12-54.81%. Thus, a combination of low-efficiency processes results in a highly efficient waste heat recovery Trinitor system, with further improvements possible through identified components' integration.
Keywords: Waste heat recovery; Polygenerative system; Trinitor components; Diesel vehicles; THERMAL-ENERGY STORAGE; PHASE-CHANGE MATERIALS; TEMPERATURE THERMOELECTRIC PROPERTIES; DIFFERENTIAL SCANNING CALORIMETRY; ALTERNATIVE CATHODE CATALYST; ACID DOPED POLYBENZIMIDAZOLE; INTERNAL-COMBUSTION ENGINES; PEM FUEL-CELL; OF-THE-ART; LATENT-HEAT; Thermodynamics; Chemistry